Providing Education and Welfare Opportunities for Syrian Children Near Conflict Zone - Burcu Güner, Pinar (ETHICS IN PROGRESS, 2020)
The article aims to 1) focus on welfare opportunities near the conflict zone in Turkey. Providing a good life for children under every condition belongs to the responsibilities of both, national and international communities. The capability approach Theory seems to promote such responsibilities at best. However, the Turkish example does not show effects as satisfactory as the German example with Turkish migrant children, which is discussed in this article and illustrated with research findings provided by the author.